Preliminary research on the externalities of forest lands in southern nigeria (2013)
The externalities of forest lands in Southern Nigeria are discussed, relating it to forests around the world. Highlights are made of the different benefits obtained from forests. Included in the discussion are the effects of forests on carbon sequestration, stabilization of weather and climate, noise abatement, benefit to hydrology, wildlife habitation, and oxygen production, socio-economic and psychological benefits amongst others.